(3GdehShYI GdJQHjI; GdYdhe GdeGOI aj cd GdMGdGJs - (3bjheLjGf, fGJGdjs ((3HjQhJs (3YhjOGJ ddfTQs, 2010)
(3Ef gOa GdeLehYI GdJQHhjI gh eQGabI GdWdGH heSGYOJge ddbjGe HCfTWI YdejI aj Uahage(B. (3CfLRJ HaVd NHQI aQjb eJNUU hHeSGYOI eYdeI ajRjGA(B. (3jJVef COhGJ JQHhjI dcd GdeYdejf(B: (3eWGHbI dJhUjGJ GdJQHjI GdhWfjI hddHQGeL GdeLOOI dJYdje GdYdhe hGdJcfhdhLjG aj GdeOGQS(B. (3Jfej gPg GdeLehYI cd CWhGQ eSjQI GdJSGDd hGdHMK, aj cd eQMdI ef gPg GdeQGMd, JQGabge dJSgjd SjQ LdSGJge, YedjI(B:(3HEdGecGf JUhjQ GdHWGbGJ GdeNUUI ddJdGejP aj eJfGhd GdWdGH CjVkG (B8 (3edUbGJ eUhQI CejfI ddfgL GdYdej GdeJHY aj GdeOGQS (B.s
(3GdfhY (B: (3cJGHs
Keywords: L$1 (Benseignement des Sciencess; Sciences education; (3JYdje GdYdhes